How the circumcision solution in Africa will increase HIV infections - Robert S. Van Howe; Michelle R. Storms (AOSIS, 2011)
The World Health Organization and UNAIDS have supported circumcision as a preventive for HIV infections in regions with high rates of heterosexually transmitted HIV; however, the circumcision solution has several fundamental flaws that undermine its potential for success. This article explores, in detail, the data on which this recommendation is based, the difficulty in translating results from high risk adults in a research setting to the general public, the impact of risk compensation, and how circumcision compares to existing alternatives. Based on our analysis it is concluded that the circumcision solution is a wasteful distraction that takes resources away from more effective, less expensive, less invasive alternatives. By diverting attention away from more effective interventions, circumcision programs will likely increase the number of HIV infections.